EFFICIENY MARKETING OF CHICKEN EGGS IN MEDAN CITY OF NORTH SUMATRA - J D Nainggolan; E Mirwandhono; A H Daulay; I Sembiring; Hamdan (Jurnal Peternakan Integratif, 2017)
The purpose of this research were to know the magnitude and affect of marketing margin cost on the selling price of chicken eggs and how the systematics of chicken egg distribution from producers to final consumers. This research was conducted at 7 markets that have been chosen by way of deliberate from 21 districts located in Medan City: Setia Budi Market, Sei Kambing Market, Sambu Market (sentral), Aksara Market, Pringgan Market, Simpang Limun Market, and Kampung Lalang Market. This research was conducted from October to November 2016. This study used primary data obtained from observation and interviews of respondents. Determination of respondents by accidental sampling metohd. The parameters studied were channel and agency marketing, marketing margin, farmer share and marketing efficiency.The result of this study indicated that the marketing institution involved were collecting traders, big traders and small traders. Marketing channels had four channels. The marketing efficiency on channel I is 2,16%, channel II is 1,14%, Channel III was 2,13% and channel IV was 1,72%. Farmer share channel I was 80,14%, channel II was 81,52%, channel III was 76,21% and channel was 81,15%. The conclusion of this research was that the marketing of chicken eggs in Medan City of North Sumatera has been efficient.